THE MINIMIZATION OF NA AGRICULTURAL PRODUCT COST FUNCTION IN FERTILIZER EXPERIMENTS - Carranza, Cristián; Gomes, F. Pimentel (REVISTA DE AGRICULTURA, 2015)
THE MINIMIZATION OF NA AGRICULTURAL PRODUCT COST FUNCTION IN FERTILIZER EXPERIMENTS